The Other End of the Kaleidoscope: Configuring Circles of Teaching and Learning - Eudora Watson; Jennifer Mitchell; Victoria Levitt (Journal of the Assembly for Expanded Perspectives on Learning, 2007)
To reflect on and participate in reconsideration of convention in academic discourse, this essay presents three voices in three genres.